Attaining the mystical body: Indian Sufi ascetic practices - Saniotis, Arthur (The Australian journal of anthropology, 2012)
While anthropologists have carefully documented various Sufi orders, the bulk of these studies focus on socio-historic and organisational aspects of Sufism. This has been especially the case of Sufis in India. There is an apparent lack of examining experiential aspects Sufi mystical practices. In India, many Sufi orders are intrinsically linked with Muslim shrines. Muslim shrines are viewed by Sufi as being invested with barkat (divine blessedness, sacred power), a power generally assumed to be a gift conferred upon the saint by Allah. Consequently, Sufis often engage in their mystical practices in the proximity of Muslim shrines. The shrine of the Sufi saint Nizamuddin Auliya, located in Delhi, is a renowned thaumatological shrine which is a centre for Sufi activities. Sufis spend many years engaged in a rigorous regimen of ascetic and mystical practices. These form a central part of their daily lives at the Nizamuddin shrine. In this article, I explore the notion of mystical mastery among Indian Sufis and ways in which their ascetic practices seek to attain a mystical body. I contend that mystical mastery is a form of re-authoring the self, in that Sufis’ mystical complexes permit them to transform and modify themselves through various operations on their bodies.